Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 11: Cephaloecetes schioettei sp. nov. from The Philippines - Just, Jean (Zootaxa, 2017)
The new species described below, Cephaloecetes schioettei, is the second siphonoecetine to be recorded from the archipelago region of Indonesia, The Philippines and Papua New Guinea. The previous reports were of Borneoecetes wongi Barnard & Thomas, 1984 from Borneo and from Papua New Guinea by Myers (1995).